2007
DOI: 10.1016/j.jcis.2007.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Formation of complex Langmuir and Langmuir–Blodgett films of water soluble rosebengal

Abstract: This communication reports the formation of complex Langmuir monolayer at the air-water interface by charge transfer types of interaction with the water soluble N-cetyl N,N,N-trimethyl ammonium bromide (CTAB) molecules doped with rosebengal (RB), with the stearic acid (SA) molecules of a preformed SA Langmuir monolayer. The reaction kinetics of the formation of RB-CTAB-SA complex monolayer was monitored by observing the increase in surface pressure with time while the barrier was kept fixed. Completion of inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The increase in surface pressure with time was recorded to have the -t curve. Surface pressure measurement was recorded using Wilhelmy plate arrangement described elsewhere [10,14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in surface pressure with time was recorded to have the -t curve. Surface pressure measurement was recorded using Wilhelmy plate arrangement described elsewhere [10,14].…”
Section: Methodsmentioning
confidence: 99%
“…These ultrathin LB films containing specific photo-functional groups or chromophore have immense importance in the field of nanotechnology based optoelectronic and photonic devices [7,9]. Although water insoluble amphiphilic molecules are ideal for LB film preparation, however, recent investigations reveal that even some water-soluble materials can form stable and well-organized Langmuir monolayer at the air-water interface [6,[10][11][12][13][14]. In some of the works it has been observed that the formation of a complex Langmuir monolayer is subjected to the adsorption of the water-soluble cationic or anionic types of materials with the oppositely charged amphiphilic molecules of a preformed Langmuir monolayer [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Langmuir-Blodgett (LB) technique has been reported the largely successful in preparing their monolayer [33]. LB technique has many potential applications in molecular electronics, non-linear optics and conducting thin films [34]. LB technique for the preparation of ultra-thin films of various organic, metallorganic and polymeric compounds plays a vital role as an action of producing molecular materials at the microscopic level [34].…”
Section: Self-assembly Of Techniquementioning
confidence: 99%
“…LB technique for the preparation of ultra-thin films of various organic, metallorganic and polymeric compounds plays a vital role as an action of producing molecular materials at the microscopic level [34]. The most important advantage of LB is that the characteristics of the films can be varied by changing LB parameters such as temperature, and molar composition [34].…”
Section: Self-assembly Of Techniquementioning
confidence: 99%
“…Langmuir-Blodgett (LB) films are known for a high degree of organization of organic molecules [2][3][4][5][6][7][8][9][10]. Recently, LB technique has been extended to the preparation of hybrid organo-clay mono-and multilayers [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%